2019
DOI: 10.1111/joor.12821
|View full text |Cite
|
Sign up to set email alerts
|

To what extent is bruxism associated with musculoskeletal signs and symptoms? A systematic review

Abstract: The aim of the present systematic review was to answer the overall research question: “To what extent is bruxism associated with musculoskeletal signs and symptoms?”. The review was performed in accordance with the PRISMA guidelines. A PubMed search of articles published until 23 November 2017 was conducted. The search string included both MeSH terms and text words. Results were presented in categories according to study design, study population (eg, adults, children), bruxism sub‐type (awake, sleep), assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 69 publications
2
40
0
4
Order By: Relevance
“…1,2 Until now, the possible relationship between bruxism and symptoms of temporomandibular disorders is still controversial in the literature due to the complexity of etiology and diagnostic of both disorders. [3][4][5] The hypothesis often discussed is the possible positive relationship between either awake or sleep bruxism and craniofacial pain is still a commonly held view in the clinical practice [3][4][5] , and sometimes even presented as a real and simple cause/effect relationship. In line with the perspective that painrelated temporomandibular disorders (TMD) must be envisaged within a biopsychosocial model of illness, and efforts to understand painful temporomandibular disorders along with other chronic pain conditions in a biopsychosocial context have been made.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Until now, the possible relationship between bruxism and symptoms of temporomandibular disorders is still controversial in the literature due to the complexity of etiology and diagnostic of both disorders. [3][4][5] The hypothesis often discussed is the possible positive relationship between either awake or sleep bruxism and craniofacial pain is still a commonly held view in the clinical practice [3][4][5] , and sometimes even presented as a real and simple cause/effect relationship. In line with the perspective that painrelated temporomandibular disorders (TMD) must be envisaged within a biopsychosocial model of illness, and efforts to understand painful temporomandibular disorders along with other chronic pain conditions in a biopsychosocial context have been made.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the perspective that painrelated temporomandibular disorders (TMD) must be envisaged within a biopsychosocial model of illness, and efforts to understand painful temporomandibular disorders along with other chronic pain conditions in a biopsychosocial context have been made. [5][6][7][8] This implies that the association between bruxism and painful temporomandibular disorders has become much more complex. 5 Orthodontists should be aware of the presence of general and awake bruxism in particular and their possible implications during an orthodontic treatment, such as the excessive use of the jaw and possible association with dental structure (e.g., dental wear and restoration failures), TMJ, and masticatory muscle damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal cohort studies using instrumental assessments of sleep bruxism on bruxism-complication-related topics, such as temporomandibular disorders 20 and tooth wear 21 are, to the best of our knowledge, absent in either published, or unpublished 22 form. It is interesting to speculate on the reason behind the absence of such studies in a research field that otherwise receives ample attention.…”
Section: Discussionmentioning
confidence: 98%
“…Besides that, it was concluded that bruxism is somehow associated with musculoskeletal symptoms. There is no support for a linear causal relationship, but the literature points more to a multifactorial relationship [51].…”
Section: Bruxism and Tooth Wearmentioning
confidence: 99%